SOSIALISASI DAN PELATIHAN PEMBIBITAN TANAMAN PALA KEPADA PETANI DI DESA PERSIAPAN URASANA KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Wattimena, Anna Yuliana; Goo, Nureni; Makaruku, Marlita H.; Tanasale, Vilma L. (Universitas Pattimura, 2024)
Nutmeg is one of the commodities in Maluku that has high economic value. The successful cultivation of nutmeg plants starts from the selection of nutmeg seeds to be used as seedlings. The use of unsuitable seedlings will cause difficulties in subsequent crop management. The problem faced preparation village urasana farmers for nutmeg cultivation is the provision of quality nutmeg seeds so that empty land in the dusung can be used for nutmeg cultivation. The purpose of this activity is the utilization of existing vacant land and improve the skills of Urasana preparation villagers for nutmeg cultivation. The target of this activity is the people of Urasana preparatory village who work as farmers. The methods used are counseling and training. Through counseling, it provides insight for farmers on how to choose healthy nutmeg seeds to be used as seedlings. The training activity provided new skills for participants to scarify nutmeg seeds to be used as seedlings. The evaluation results showed that after conducting counseling and training on nutmeg plant nurseries, participants' knowledge and skills increased by 75-100%.